IClone 4.31 3D animation : beginner's guide : animate your stories and ideas to create realistic scenes with this movie making application geared towards new and inexperienced film makers, video producers/compositors, vxf artists, and 3D artists/designers /: beginner's guide : animate your stories and ideas to create realistic scenes with this movie making application geared towards new and inexperienced film makers, video producers/compositors, vxf artists, and 3D artists/designers. (2011) - Unknown
No abstract available